Implementasi Metode Talaqqi dalam Pembelajaran Tahfidz Al-Quran bagi Anak Berkebutuhan Khusus - Laili Nur Umayah; Muhammad Misbah (MAGHZA, 2021)
This article aims to describe the use of the Talaqqi method in learning Tahfidz Al-Quran in SMP Boarding School Putra Harapan Purwokerto especially for children with special needs (ABK). The data is collected using observation methods, structured free interviews, and documentation. Data analysis using the steps offered by Miles & Huberman, data reduction, data display, and conclusion. The results of this research are that the implementation of the Talaqqi method in learning Tahfidz Al-Quran for children with special need, performed every morning for 15-30 minutes in the inclusion classroom. The steps used by the teacher are to teach directly (musyafahah) with students one by one, teachers repeat reading verses of the Qur'an by 5 times while emphasizing the movement of lips and special touch for the student so that he can capture the reading of the verse correctly. The success is supported also by the patience and sincerity of teachers in guiding, motivating, and understanding the true characteristics of students with special needs.